Retraction Note: Prevalence of Musculoskeletal Pain Due to Smart Phone Usage Among High School Students-A Crosssectional Study: Musculoskeletal Pain due to Smart Phone usage - Khalid, Amna; Ahmad, Jawad; Sarfraz, Ramish; Iqbal, Ayesha; Arshad, Areeba; Zahid, Hamza (Pakistan Journal of Health Sciences, 2022)
Retraction Note: The Editors-in-Chief have retracted this article. After publication, concerns were raised from the original author as this publication was proceeded with his consent by his supervisor. As supervisor requests to retract the article by sharing original authors current supervisor email where this study was originally conducted (Xi'an Jiaotong University). The Editors-in-Chief therefore consider the conclusion to retract this article as it is published without the consent and published without including the main author in author list.